Faktor-Faktor Yang Mempengaruhi Integritas Laporan Keuangan Di BEI - Vera waty; Icahya Robika (LPPM Universitas Multi Data Palembang, 2023)
Financial reports are information tools that connect companies with interested parties, which show thecompany’s financial health condition and company performance. This study aims to examine firm size, leverage,audit period, and independent commissioners that affect the integrity of financial statements. The population usedin this study are food and beverage companies listed on the Indonesia Stock Exchange in 2018-2020. This studyused purposive sampling in the selection of samples and obtained 13 companies with 35 samples. Analysis of thedata used is multiple linear regression analysis with the help of SPSS program. Firm size and audit period variableshave a positive effect on the integrity of financial statements, while leverage and independent commissioners haveno effect on the integrity of financial statements.